The Study of the Evolvement Rule of Product Modeling Features Based on Big Data — Taking the Sense of Decoration as an Example - Haiyang Yu, Jia Qin, Keheng Zhao (Forest Chemicals Review)
As time goes by, the modeling design of industrial products changes continuously in style. The grasp of its evolvement rule will be helpful for product design and manufacturers to predict the direction of its change in order to design the models of products that can meet the aesthetic demands of customers better. With the advent of the age of big data, it is more convenient to study the evolvement rule of product modeling features through the collection, arrangement and analysis of historical data. This study takes “the sense of decoration” of modeling styles of mainstream products in the hundred years of the 20th century as its object to quantify the modeling feature and then analyze the data in order to find out the corresponding evolvement rule. After that, the study analyzes the reasons for the formation of the rule, and puts forward the referential thought to improve the study combining with related technologies of AI in the further study.